User Name Remember Me? Password

 Advanced Statistics Advanced Probability and Statistics Math Forum

 January 13th, 2015, 11:31 AM #1 Senior Member   Joined: Jul 2013 From: United Kingdom Posts: 471 Thanks: 40 Standard Deviation Formulas - Short Proof Today I learnt that: $\displaystyle Variance=\frac { \Sigma { \left( x-\overline { x } \right) }^{ 2 } }{ n } =\frac { \Sigma { x }^{ 2 } }{ n } -{ \left( \frac { \Sigma x }{ n } \right) }^{ 2 }$ Considering that the formula for the mean in the United Kingdom is: $\displaystyle \overline { x } =\frac { \Sigma x }{ n }$ Now, I wasn't told why the formulas posted above were equal to one another. I was just supposed to accept such truths without any evidence. So, to satisfy such claims - I've made a short little proof as to why the two formulas at the top of your screen ARE in fact equal to one another. If you have any better proofs, then please feel free to post them on this thread. For the meantime, this is what I've achieved... ---------------------------------------------------- PROOF: Say that: $\displaystyle For\quad convenience,\\ \\ d=a+b+c,\\ \\ \therefore \quad \frac { \Sigma x }{ n } =\frac { a+b+c }{ n } =\frac { d }{ n } =\overline { x } \\ \\ However,\quad \frac { d }{ n } =p,\quad \therefore \quad \overline { x } =p,\quad d=np\quad and\quad n=\frac { d }{ p } .\\ \\ Note\quad that:\quad n=3\quad in\quad this\quad case.$ Also note that: $\displaystyle { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }=g,\\ \\ \therefore \quad \frac { \Sigma { x }^{ 2 } }{ n } =\frac { { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 } }{ n } =\frac { g }{ n } \\ \\ However,\quad \frac { g }{ n } =q,\quad \therefore \quad g=nq\quad and\quad n=\frac { g }{ q } .$ Now, with these set of rules, we should reach the conclusion that: $\displaystyle \frac { \Sigma { x }^{ 2 } }{ n } -{ \left( \frac { \Sigma x }{ n } \right) }^{ 2 }=\frac { g }{ n } -{ \left( \frac { d }{ n } \right) }^{ 2 }=q-{ p }^{ 2 }$ We can also discover that: $\displaystyle \frac { \Sigma { \left( x-\overline { x } \right) }^{ 2 } }{ n } \\ \\ =\frac { { \left( a-p \right) }^{ 2 }+{ \left( b-p \right) }^{ 2 }+{ \left( c-p \right) }^{ 2 } }{ n } \\ \\ =\frac { { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }+3{ p }^{ 2 }-2ap-2bp-2cp }{ n } \\ \\ =\frac { g+3{ p }^{ 2 }-2p\left( a+b+c \right) }{ n } \\ \\ =\frac { g+3{ p }^{ 2 }-2pd }{ n } \\ \\ =\frac { g }{ n } +\frac { 3{ p }^{ 2 } }{ n } -\frac { 2pd }{ n } \\ \\ \boxed { But,\quad n=3. } \\ \\ =q+{ p }^{ 2 }-2p\cdot \frac { d }{ n } \\ \\ =q+{ p }^{ 2 }-2{ p }^{ 2 }\\ \\ =q-{ p }^{ 2 }$ So, as: $\displaystyle q-{ p }^{ 2 }=q-{ p }^{ 2 }\\ \\ \frac { \Sigma { \left( x-\overline { x } \right) }^{ 2 } }{ n } =\frac { \Sigma { x }^{ 2 } }{ n } -{ \left( \frac { \Sigma x }{ n } \right) }^{ 2 }$ I came up with this proof, as I wasn't told why these two formulas are equal to one another. Hopefully this will be able to help some maths students come to terms with why it's the case. If you have any better proofs, please post them below. Thankyou for your attention. Last edited by perfect_world; January 13th, 2015 at 11:33 AM. January 13th, 2015, 02:01 PM #2 Global Moderator   Joined: May 2007 Posts: 6,807 Thanks: 717 $\displaystyle \sum \frac{(x-m)^2}{n}=\sum (\frac{x^2}{n}-2\frac{mx}{n}+\frac{m^2}{n})$ $\displaystyle \sum \frac{mx}{n} = m\sum \frac{x}{n} = m^2$ $\displaystyle \sum \frac{m^2}{n} = m^2 \sum \frac{1}{n} =m^2$ Put it all together to get result. January 13th, 2015, 03:59 PM   #3
Senior Member

Joined: Oct 2013
From: New York, USA

Posts: 661
Thanks: 87

Quote:
 Originally Posted by mathman $\displaystyle \sum \frac{(x-m)^2}{n}=\sum (\frac{x^2}{n}-2\frac{mx}{n}+\frac{m^2}{n})$ $\displaystyle \sum \frac{mx}{n} = m\sum \frac{x}{n} = m^2$ $\displaystyle \sum \frac{m^2}{n} = m^2 \sum \frac{1}{n} =m^2$ Put it all together to get result.
I understand that you multiplied the binomial in the first line, but I have no idea how you got to the second line. January 14th, 2015, 12:44 PM #4 Global Moderator   Joined: May 2007 Posts: 6,807 Thanks: 717 In $\displaystyle \sum \frac {mx}{n}$, m is constant, so take it outside summation. By definition: $\displaystyle \sum \frac{x}{n} = m$. January 15th, 2015, 10:32 AM #5 Senior Member   Joined: Jul 2013 From: United Kingdom Posts: 471 Thanks: 40 To @mathman, In your proof I presume that n=1, as the data set for x consists of x alone. It's funny how that summation sign can be manipulated around in specific cases. How would I define this data set mathematically? Would it be: x={x} Therefore n=1. Last edited by perfect_world; January 15th, 2015 at 10:35 AM. January 15th, 2015, 10:51 AM #6 Senior Member   Joined: Jul 2013 From: United Kingdom Posts: 471 Thanks: 40 Can you let me know if I'd be able to manipulate the sigma symbol in such a manner... $\displaystyle \frac { \Sigma { \left( x-m \right) }^{ 2 } }{ n } \\ =\sum { \frac { { \left( x-m \right) }^{ 2 } }{ n } } \\ \\ =\sum { \frac { { x }^{ 2 }-2mx+{ m }^{ 2 } }{ n } } \\ \\ =\sum { \left( \frac { { x }^{ 2 } }{ n } -2\frac { mx }{ n } +\frac { { m }^{ 2 } }{ n } \right) } \\ \\ =\sum { \frac { { x }^{ 2 } }{ n } } -2\sum { \frac { mx }{ n } } +\sum { \frac { { m }^{ 2 } }{ n } } \\ \\ =\frac { \Sigma { x }^{ 2 } }{ n } -2{ m }^{ 2 }+{ m }^{ 2 }\\ \\ =\frac { \Sigma { x }^{ 2 } }{ n } -{ m }^{ 2 }\\ \\ =\frac { \Sigma { x }^{ 2 } }{ n } -{ \left( \frac { \Sigma x }{ n } \right) }^{ 2 }$ I'm just experimenting with it, and seeing if it's possible to create proofs in this way. January 15th, 2015, 11:47 AM   #7
Senior Member

Joined: Jul 2013
From: United Kingdom

Posts: 471
Thanks: 40

Quote:
 Originally Posted by EvanJ I understand that you multiplied the binomial in the first line, but I have no idea how you got to the second line.
@EvanJ,

I believe that these truths can be derived from the information we have at our disposal.

$\displaystyle x=\left\{ x \right\} \Rightarrow n=1\\ \\ \frac { \Sigma x }{ n } =\frac { x }{ n } =\sum { \frac { x }{ n } } \\ \\ ---------------------------\\ \\ m=\frac { \Sigma x }{ n } ,\\ \\ \therefore \quad { m }^{ 2 }=m\frac { \Sigma x }{ n } =\frac { mx }{ n } =m\sum { \frac { x }{ n } } =\frac { \Sigma mx }{ n } \\ \\ ----------------------------\\ \\ \frac { \Sigma { x }^{ 2 } }{ n } =\frac { { x }^{ 2 } }{ n } =x\cdot \frac { x }{ n } =x\frac { \Sigma x }{ n } =x\sum { \frac { x }{ n } } \\ \\ -----------------------------\\ \\ \frac { { m }^{ 2 } }{ n } ={ m }^{ 2 }\sum { \frac { 1 }{ n } } =\frac { { \left( \frac { \Sigma x }{ n } \right) }^{ 2 } }{ n } ={ \left( \frac { \Sigma x }{ n } \right) }^{ 2 },\quad (as\quad n=1)\\ \\ \\ \\ \\ \\ \\ \\$ January 15th, 2015, 05:31 PM #8 Global Moderator   Joined: May 2007 Posts: 6,807 Thanks: 717 I believe that in the original expression $\displaystyle x$ was meant to be $\displaystyle x_i$ (one sample) where i went from 1 to n. My answers were made on that assumption. Tags deviation, formulas, proof, short, standard Search tags for this page

,

### standard deviation proof

Click on a term to search for related topics.
 Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Similar Threads Thread Thread Starter Forum Replies Last Post tjthedj Probability and Statistics 3 December 18th, 2014 07:09 AM green21317 Probability and Statistics 1 May 30th, 2014 12:23 PM scarr Advanced Statistics 2 March 15th, 2012 01:53 AM Axel Algebra 2 April 28th, 2011 03:25 AM daniela Algebra 1 September 18th, 2007 02:50 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top

Copyright © 2019 My Math Forum. All rights reserved.      